2003
DOI: 10.1128/iai.71.5.2693-2703.2003
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Inflammatory and Immune Responses in the Early Stages of ChronicHelicobacter pyloriInfection

Abstract: The early consequences of Helicobacter pylori infection and the role of bacterial virulence determinants in disease outcome remain to be established. The present study sought to measure the development of host inflammatory and immune responses and their relationship to the putative bacterial virulence factors cag pathogenicity island (cagPAI), vacA allele, and oipA in combination with bacterial colonization density in a feline model of the early stages of H. pylori infection. Gastric tissues obtained from infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 72 publications
3
31
0
2
Order By: Relevance
“…Otherwise, H. pylori DNA was not detected in the liver of patients with alcoholic cirrhosis and those with autoimmune hepatitis. In agreement with previous studies (Straubinger et al 2003, Algood & Cover 2006, Lafdil et al 2010, we confirmed the strong Th1 proinflammatory response with increased levels of IFN-γ, the Th1 signature cytokine, in these patients. We F: female; M: male; n: number of subjects; SD: standard deviation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Otherwise, H. pylori DNA was not detected in the liver of patients with alcoholic cirrhosis and those with autoimmune hepatitis. In agreement with previous studies (Straubinger et al 2003, Algood & Cover 2006, Lafdil et al 2010, we confirmed the strong Th1 proinflammatory response with increased levels of IFN-γ, the Th1 signature cytokine, in these patients. We F: female; M: male; n: number of subjects; SD: standard deviation.…”
Section: Discussionsupporting
confidence: 80%
“…IL-10 can suppress the immune response against pathogens, including those of the genus Helicobacter (Algood & Cover 2006), mainly by inhibiting IFN-γ. IFN-γ is considered an essential molecule for the control of intracellular pathogens, but also acts against Helicobacter (D'Elios et al 1997, Straubinger et al 2003. The recently discovered pro-inflammatory Th17 cell and its major inflammatory cytokine, IL-17A, have the capacity to confer protection against extracellular bacteria, among them, H. pylori (Caruso et al 2007).…”
mentioning
confidence: 99%
“…The gastric lymphoid follicles consist mainly of IgM + B cells surrounded by clusters of CD4 + and CD8 + T cells [21]. More recent studies [47] have sought to characterise the cellular and cytokine changes in gastric tissues that occur during the early stage of infection in cats. The initial mucosal response was associated with an increase in the levels of IFNγ, IL1α, IL-1β and IL-8 mRNA with secondary lymphoid follicles infiltrated with BLA.36 positive cells (progenitor B cells), CD79α positive cells (reactive B cells), and CD3 positive T cells.…”
Section: Mucosal Cytokines and The Response To Mucosal Infectionmentioning
confidence: 99%
“…In particular, the pluripotent pro-inflammatory cytokine IL-1b has a central role in the pathogenesis of Helicobacter pylori-induced mucosal inflammation (Guiraldes et al, 2001;Maeda et al, 2001;Straubinger et al, 2003). IL-1b gene expression and protein production are increased in H. pylori infection and reduced with successful eradication (Wang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%